Comparisons of β2-microglobulin, apolipoprotein A1, and immunoglobulins (IgG and IgM) detected in the serum and urine from individual cats - Katagi, Michio; Imatomi, Haruka; Tsuchida, Yasushiko; Katayama, Kinya; Yoshikawa, Yasunaga; Orino, Koichi (Austral Journal of Veterinary Sciences, 2023)
The detection of serum and urinary proteins is important for normal conditions, but comparisons of individual serum and urine proteins are rarely performed. The aim of this study was to examine β2-microglobulin (β2-MG), apolipoprotein A-I (ApoA-I), and immunoglobulins (IgG and IgM) in the serum and urine of cats with chronic kidney disease and lower urinary tract disease (LUTD), in addition to healthy cats. Serum and urine samples were analyzed by sodium dodecyl sulfate–polyacrylamide gel electrophoresis, followed by immunoblotting for β2-MG, ApoA-I, IgG, and IgM. The molecular weight of serum β2-MG was greater than the predicted molecular weight (11,472 Da), and different types of modified β2-MGs were detected in the urine of healthy and diseased cats, including the original type, in addition to the grycocylated and partially digested types. Serum and urinary ApoA-I molecular weights were lower than the predicted molecular weight (28,943 Da), and high levels of urinary ApoA-I were detected in LUTD cats, although urinary ApoA-I was not detected in healthy cats. Under non-reducing conditions, the H-chains of urinary IgM pentamers and IgG monomers were detected in healthy cats. These results suggest that urinary β2-MG is modified in a different manner from serum β2-MG, urinary ApoA-I is a potential marker of LUTD, and urinary IgM pentamer, IgG monomer, and their glomerular filtration, even in healthy conditions.